Safety Standard Of River Transportation (Speedboat) In Musi Port Of River Pasar 16 Ilir Palembang - Kodrat Alam (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2020)
South Sumatra is one of the provinces that has a large area of ​​water. Musi River is the main means of transportation in several sub-districts in South Sumatra. The problem discussed in this study is